The Information Value, Salience, and Framing of Road Signs in Singaraja - Suta Paramarta, I Made (International Seminar on Austronesian Languages and Literature; Vol 9 No 1 (2021): PROCEEDINGS International Seminar on Austronesian Languages and Literature IX (ISALL IX), 2021)
This paper reveals the language presentations of the road signs in Singaraja, the capital city of Buleleng regency in North Bali, through multimodal compositions theory proposed by Kress and Van Leeuwen, which includes information value, salience, and framing. The research design is a single case study with the subjects of 4 road signs in Singaraja. The four road signs are chosen purposively from 151 road signs. In order to gather the data, those road signs were photographed using a digital camera. Each group is presented differently by the maker of the signs, in this case, the department of transportation of Buleleng Regency, which is under traffic regulation in Indonesia, especially Bali. The four categories are varied in terms of the languages presented on the road signs, namely monolingual Indonesian, Indonesian and Balinese combination, Balinese and Indonesian combination. The findings show that the information value is presented mostly using a top-down relation. The road signs present information value using Balinese and Indonesian languages less consistently. Either Indonesian or Balinese language takes their position as the ideal part on the signs. The salience is reflected by the presence of the Indonesian language in capital letters with relatively a larger size, which is more readable from a distance than the Balinese letters. The framing analysis shows that the bilingual road signs are separated using a line which indicates that Indonesian and Balinese words convey unrelated information. However, they contain one message to the sign readers